Barriers and Challenges in Managing Hypertension in Belitung, Indonesia: A Qualitative Study - Aungsuroch, Yupin; Gunawan, Joko; Polsook, Rapin; Anuruang, Sakuntala; Phongphibool, Sitha; Nazliansyah, Nazliansyah (Nurse Media Journal of Nursing, 2021)
Background: The Government of Indonesia has provided a Chronic Disease Management Program, better known as PROLANIS, to reduce the incidence of hypertension; however, the prevalence of hypertension remains high in the community, especially in Belitung, Indonesia, which warrants further investigation. One of the strategies to decrease the number of hypertensions is by addressing barriers and challenges in hypertension management according to patients’ points of view, which has become a lack of focus in previous studies.Purpose: This study aimed to explore the barriers and challenges of patients in managing hypertension in Belitung, Indonesia.Methods: This research employed a qualitative descriptive study design with 20 hypertensive patients who had access to the PROLANIS program in public health centers. Focus group discussions were conducted for data collection. The content analysis was used for data analysis.Results: Six themes were developed from the data, including (1) Dietary habits: the role of salt, (2) Nonadherence to medication due to the use of traditional medicine, (3) Shopping habit on nonprescription medication, (4) Confusion of anti-hypertensive drugs, (5) Barriers to physical exercise, and (6) Health monitoring and education.Conclusion: This study serves as an input for nurses and healthcare providers to improve the PROLANIS program, especially in hypertension management, as well as to develop new nursing interventions according to the barriers and challenges.